Arctic charr (Salvelinus alpinus (L.)), an adequate host to Gyrodactylus salaris (Monogenea) - Winger, Anja Celine (Universitetet i Tromsø, 2009)
The papers of the thesis are not available in Munin: 1. Anja C. Winger, Marte Kanck, Roar Kristoffersen and Rune Knudsen: «Seasonal dynamics and persistence of Gyrodactylus salaris in two riverine anadromous Arctic charr populations», Enviromnetal biology of fishes, 2008,83,117-123 (Springer; publisher's restrictions), available at http://dx.doi.org/10.1007/s10641-007-9274-x 2. A. C. Winger, R. Kristoffersen, S. I. Siikavuopio and R. Knudsen: «Experiments to test if allopatric Salvelinus alpinus are suitable year-round hosts of Gyrodactylus salaris (Monogenea)», Journal of Fish Biology (2009) 74, 1476–1486 (Wiley-Blackwell; publisher's restrictions), available at http://dx.doi.org/10.1111/j.1095-8649.2009.02215.x 3. A. C. Winger, R. Primicerio, R. Kristoffersen, S. I. Siikavuopio and R. Knudsen: «Gyrodactylus salaris infecting allopatric Arctic charr Salvelinus alpinus fry: an experimental study of host survival», Journal of Fish Biology (2008) 73, 2198–2209 (Wiley-Blackwell; publisher's restrictions), available at http://dx.doi.org/10.1111/j.1095-8649.2008.02056.x 4. A. C. Winger, R. Knudsen, R. Primicerio and R. Kristoffersen: «Infrapopulation dynamics and the role of transmission in the hyperviviparous Gyrodactylus salaris (Monogenea)» (manuscript) Arctic charr is a suitable host to Gyrodactylus salaris, and G. salaris is a non-pathogen to this host species. This parasite is highly pathogenic to Norwegian Atlantic salmon and it has driven most affected salmon populations to extinction. In Troms County in northern Norway, two rivers are infected. These two rivers, Skibotnelva and Signaldalselva, are the northernmost G. salaris infected rivers in Norway and the natural salmon populations are regarded extinct or close to extinction due to the parasite. Skibotnelva has been treated twice with the plant poison rotenone. Both treatments failed, and an ongoing hypothesis is that the occurrence of Arctic charr is the main cause of this. The overall aim of this study was to elucidate the role of Arctic charr as a ...